INEQUALITIES IN HEALTH STATUS DEPENDING ON SOCIO-ECONOMIC SITUATION IN THE EUROPEAN COUNTRIES - Pacáková, Viera; Kopecká, Lucie (My University, 2018)
There are a number of major studies which have demonstrated a clear link between socio-economic background (such as income or occupation) and health. The goal of this article is to assess and quantify inequalities in health status of inhabitants depending on socio-economic situation in European countries based on selected social and health indicators in two different periods. The earlier period is the year 2000, and the later period is the year 2015 or the most recent years. The results of the analysis based on multidimensional statistical methods should give an answer to the question as to whether and how strongly the socio-economic situation in the countries of Europe affects the health status of the population and how the situation has changed over the course of 15 years. In accordance with the stated objectives we have chosen 15 variables (source: WHO, OECD, Eurostat). These variables (indicators) together characterize the quality of life in terms of socio-economic situation and state of health of citize s in 22 selected European countries. The choice of countries was mainly infl uenced by the availability of data of the selected variables in the both years 2000 and 2015. According to the above mentioned goals of the article we have used factor analysis, cluster analysis and multidimensional comparative analysis methods on data sets of health and socio-economic indicators in the both years. The results of the application of these multidimensional statistical methods, their comparisons and comparisons over time can provide information on whether the targets of the European Commission and the OECD to reduce health inequalities, depending on the socio-economic situation in European countries, in the period from 2000 to 2015 have been achieved.
NEROVNOSTI VE STAVU ZDRAVÍ V ZÁVISLOTI NA SOCIÁLNĚ EKONOMICKÉ SITUACI V EVROPSKÝCH ZEMÍCH
Keywords: Health; socio-economic situation; inequalities; multidimensional statistical methods.; Zdraví; sociálně ekonomická situace; nerovnosti; vícerozměrné statistické metody.